2016
DOI: 10.1016/j.jip.2016.06.001
|View full text |Cite
|
Sign up to set email alerts
|

The mass mortality of blue mussels (Mytilus spp.) from the Atlantic coast of France is associated with heavy genomic abnormalities as evidenced by flow cytometry

Abstract: Since 2014, France's blue mussel industry has been facing heavy mortality outbreaks (90-100%) affecting both juveniles and adults. This report presents evidence of heavy genomic abnormalities associated with mortality outbreaks in blue mussels, Mytilus edulis-galloprovincialis, from the Atlantic coast of France. In this study, ploidy characteristics of hemic cells were investigated using Flow CytoMetry (FCM), revealing an unusual, broad continuum of ploidy distribution from hypodiploidy to tetraploidy. FCM was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 30 publications
0
34
0
Order By: Relevance
“…Mass mortalities of various bivalve species have been associated with disseminated neoplasia (see reviews by Elston et al, 1992;Carballal et al, 2015). In France, Benabdelmouna & Ledu (2016) observed that genomic abnormalities, namely aneuploidy of the hemolymph cells, were significantly correlated with…”
Section: Lesions and Alteration: Hemocytic Infiltration Granulocytommentioning
confidence: 99%
See 1 more Smart Citation
“…Mass mortalities of various bivalve species have been associated with disseminated neoplasia (see reviews by Elston et al, 1992;Carballal et al, 2015). In France, Benabdelmouna & Ledu (2016) observed that genomic abnormalities, namely aneuploidy of the hemolymph cells, were significantly correlated with…”
Section: Lesions and Alteration: Hemocytic Infiltration Granulocytommentioning
confidence: 99%
“…(Moore et al, 1991), including M. trossulus in Washington and Oregon (USA) and in British Columbia (Canada) (Elston et al, 1992). In France, Benabdelmouna & Ledu (2016) and Benabdelmouna et al (2018) presented evidence of the involvement of genomic abnormalities in mortality outbreaks in blue mussels and linked them to disseminated neoplasia. In addition, some cases of disseminated neoplasia in Mytilus edulis from Lannion (northern Brittany, France) were observed in mid-October 2016 by Burioli et al (2017) during a mortality event.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, their roles on mortality outbreak in French cultured mussel populations are still unknown. In addition, recent studies indicated that the mortality level of blue mussel stocks in France appeared to be significantly correlated to genomic abnormalities detected by flow cytometric analyses of hemolymph (Benabdelmouna and Ledu 2016). These genomic abnormalities could be reflected environmental contaminations or also could be the sign of a potential disseminated neoplasia disease.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Work is still on progress regarding these hydrodynamic-pathological linked aspects of the winter 2014 mortality event. Very recently, a studied carried out by Benabdelmouna and Ledu (2016) reported heavy genomic abnormalities (GA) associated with blue mussel mortality outbreaks observed in March of 2014 in the sound. They particularly showed that mussel cultivated stocks with high GA% values presented high mortality levels.…”
Section: Accepted Manuscriptmentioning
confidence: 99%